2014
DOI: 10.1101/gr.162008.113
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of H3K27me3-marked chromatin is linked to gene expression evolution and to patterns of gene duplication and diversification

Abstract: Histone modifications are critical for the regulation of gene expression, cell type specification, and differentiation. However, evolutionary patterns of key modifications that regulate gene expression in differentiating organisms have not been examined. Here we mapped the genomic locations of the repressive mark histone 3 lysine 27 trimethylation (H3K27me3) in four species of Drosophila, and compared these patterns to those in C. elegans. We found that patterns of H3K27me3 are highly conserved across species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
3
18
0
Order By: Relevance
“…In fact, the evolutionary profile of epigenomic domain organization in embryos of five Drosophila species indicates a complete lack of divergence of H3K27me3-marked Polycomb domains in syntenic regions. A similar high conservation of the H3K27me3 pattern across Drosophila species was recently described (Arthur et al, 2014). Polycomb domains typically harbor several PH-marked PREs, and a comparative analysis showed that these are also highly conserved and the few loci that show a divergence of PRC1 occupancy patterns are not correlated with overall domain divergence.…”
Section: Multilayer Organization and The Evolutionary Buffering Of Pomentioning
confidence: 80%
“…In fact, the evolutionary profile of epigenomic domain organization in embryos of five Drosophila species indicates a complete lack of divergence of H3K27me3-marked Polycomb domains in syntenic regions. A similar high conservation of the H3K27me3 pattern across Drosophila species was recently described (Arthur et al, 2014). Polycomb domains typically harbor several PH-marked PREs, and a comparative analysis showed that these are also highly conserved and the few loci that show a divergence of PRC1 occupancy patterns are not correlated with overall domain divergence.…”
Section: Multilayer Organization and The Evolutionary Buffering Of Pomentioning
confidence: 80%
“…Functional analyses suggest that Zeus evolved specific roles in the development and function of Drosophila sperm and testis 2 . This evolution in Zeus' function coincided with changes in its expression and patterns of histone modification at the Zeus locus 11 . In contrast, its parental gene Caf40 (CG14213, also known as Rcd-1), conserved across eukaryotes, is ubiquitously expressed and is essential for viability in Drosophila melanogaster 2 …”
Section: Introductionmentioning
confidence: 85%
“…However, as introduced previously, although epigenetic modifications are also important in regulating gene expression and are well studied in various biological processes, it is rarely explicitly studied in the new gene origination process. Nevertheless, some exciting results are just emerging as demonstrated in a few very recent studies on how epigenetic evolution accompanied transcriptional divergence of duplicated genes (Arthur et al, 2014;Keller & Yi, 2014;Wang et al, 2014). Different from these pioneering works, we directly examined how various histone modifications evolve dynamically across hundreds of million years by classifying genes into more than 10 different age groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, although epigenetic mechanisms are also critical to gene expression regulation (Kouzarides, 2007;Li et al, 2007;Brown & Bachtrog, 2014), little is known about their roles in expressional evolution of new genes. It was not until very recently that two important epigenetic mechanisms, that is, DNA methylation and histone modifications, were found to be implicated in the transcriptional divergence of duplicated new genes and their parental copies (Arthur et al, 2014;Keller & Yi, 2014;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%